Burst properties of the highly active FRB20201124A using uGMRT. Issue 2 (22nd October 2021) - Marthi, V R; Bethapudi, S; Main, R A; Lin, H-H; Spitler, L G; Wharton, R S; Li, D Z; Gautam, T; Pen, U-L; Hilmarsson, G H
ABSTRACT: We report the observations of the highly active FRB20201124A with the upgraded Giant Metrewave Radio Telescope (uGMRT) at 550–750 MHz. These observations in the incoherent array mode simultaneously provided an arcsecond localization of bursts from FRB20201124A, the discovery of persistent radio emission associated with the host galaxy, and the detection of 48 bursts. Using the brightest burst in the sample ( F = 108 Jy ms), we find a structure-maximizing dispersion measure of 410.8 ± 0.5 pc cm −3 . We find that our observations are complete down to a fluence level of 10 Jy ms, above which the cumulative burst rate scales as a power law R(\!F) = 10 h^-1 (F/10 Jy ms)^γ , with γ = −1.2 ± 0.2. We find that the bursts are, on average, wider than those reported for other repeating fast radio bursts (FRBs). We find that the waiting time between bursts is well approximated by an exponential distribution with a mean of ∼2.9 min during our observations. We searched for periodicities using both a standard Fourier domain method and the fast folding algorithm, but found no significant candidates. We measure bulk spectro-temporal drift rates between −0.75 and −20 MHz ms −1 . Finally, we use the brightest burst to set an upper limit to the scattering time of 11.1 ms at 550 MHz. The localization of FRB20201124A adds strength to the proof-of-concept method described in our earlier work and serves as a potential model for future localizations and follow-up of repeating FRBs with the uGMRT.